THE LEVEL OF THE SOCIETY DEVELOPMENT AND BURIAL FORMS (ACCORDING TO THE MATERIALS OF EASTERN EUROPE OF THE EARLY IRON AGE) (City: History, Culture, Society, 2021)
The burial rites of the tribes of the different natural zones of Eastern Europe during the Early Iron Age are analyzed in this paper. There were various ways of treating with the deceased.For most of the late primitive tribes of the forest zone, information about the burial rite is absent in fact. One can assume the existence of the traditions that did not provide the preservation of the remains of the deceased in any form.The population of the Forest-Steppe had a developed cult of the ancestors, which was expressed in the veneration of their remains. The body could be buried in flat or burial mound cemeteries, on the territory of the settlement (in economic or residential buildings, special graves). The bones of the deceased after exposure could be stored in the settlement.The materials testify the existence of the archaic customs of the treatment with the body of the deceased among the tribes of the Forest and Forest-steppe zones. Among the Scythians of the Northern Black Sea, these elements are not recorded.
Keywords: Eastern Europe; funeral rites; level of the development of society; Early Iron Age